2023
DOI: 10.1242/dev.201472
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage signals from somatic uterine tissue arrest oogenesis through activated DAF-16

Abstract: Germ line integrity is critical for progeny fitness. Organisms deploy the DNA damage response (DDR) signaling to protect the germ line from genotoxic stress, facilitating the cell-cycle arrest of germ cells and DNA repair or their apoptosis. Cell-autonomous regulation of germ line quality in response to DNA damage is well-studied; however, how quality is enforced cell non-autonomously on sensing somatic D NA damage is less known. Using Caenorhabditis elegans, we show that DDR disruption, only in the uterus, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In a recent study, we described the crosstalk of the cyclin-dependent protein kinase, cdk-12 with the IIS pathway to regulate germ cell development (Sarkar et al, 2023). Interestingly, in that study, the function of the cdk-12 was found to be independent of its canonical cyclin, cyclin K/ccnk-1 (Blazek et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, we described the crosstalk of the cyclin-dependent protein kinase, cdk-12 with the IIS pathway to regulate germ cell development (Sarkar et al, 2023). Interestingly, in that study, the function of the cdk-12 was found to be independent of its canonical cyclin, cyclin K/ccnk-1 (Blazek et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, we also find that cyd-1 regulates oocyte quality and pachytene arrest of the germ cells, cell non-autonomously from the somatic gonad (uterus) under wild-type and low IIS, respectively ( Figure 7 ) . We have previously demonstrated that somatic DNA damage triggers DAF-16/FOXO-dependent stalling of oogenesis under low IIS in a cell non-autonomous manner (Sarkar et al, 2023). In a different context, somatic ERK/MPK-1 (Robinson-Thiewes et al, 2021) and kri-1 (Ito et al, 2010) have been shown to influence germ cell proliferation and death, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this direction, our recent study with one such identified kinase hit, B0285.1/CDK-12, shows that it is crucial for maintaining DNA integrity. We used CDK-12 as a genetic tool to analyze the effects of tissue-specific DDR perturbation and DNA damage in the IIS pathway mutants 56 . We found that knocking down cdk-12 only in the somatic uterine tissue of the IIS pathway mutants led to a DAF-16-dependent pachytene arrest of germ cells.…”
Section: Discussionmentioning
confidence: 99%